Shape and Size of Dental Arch - Dostálová, T.; Tauferová, E.; Teuberová, Z.; Seydlová, M.; Smutný, V.; Racek, J.; Bartonova, M. (Methods of Information in Medicine, 2006)
Objectives: The diagnostic procedure commences with the initial examination, during which a number of individual findings of the occlusion or malocclusion are clarified [1]. The objective is to describe the morphological and functional characteristics on each patient using specific guidelines, and then to provide a prognosis of the therapy. Upper and lower arch compression in first premolars and molars area was visible before treatment.Methods: A special device (Czech technical university research prototype) was prepared for this purpose. The optical head contains a digital color camera. The front of the optical head consists of a removable prism which is put into the mouth. The findings can display live images from the camera, which can be archived on a PC. The device captured and geometrically calibrated images permitting comparison of several different dental casts.Results: In the first part of this study 792 sets of study plaster casts were screened. Measurements of dental arch width between reference points of canines, first premolars and first molars were made: upper jaw: men: 3-3 – 35.1 mm (SE 0.13); 4-4 – 37.5 mm (SE 0.13); 6-6 – 48.1 mm (SE 0.19); women: 3-3 – 33.4 mm (SE 0.13); 4-4 – 35.6 mm (SE 0.15); 6-6 – 46.7 mm (SE 0.19). The second part concerns the group of 36 patients which is different from the 792 controls. There were studied changes between initial, post-treatment and post-retention alignment of upper and lower dental arch.Conclusions: Geometrically calibrated images help compare several different steps of the treatment and show a significant difference between patients before and after treatment.
Keywords: Ortodontics; prosthetics; dental arch width; cast